Halal Tourism Development In Japan : A Literature Review On Challenges and Opportunities For Muslim Tourists - Nurul Septiani; Badrah Uyuni; Sarbini Anim (Civiliza Publishing, 2026)
This study aims to analyze the development of halal tourism in Japan and to identify the challenges and opportunities in meeting the needs of Muslim tourists. This study employs a qualitative literature review approach through thematic analysis of scholarly articles, report, and official publications published between 2016-2026 related to halal Japan. The findings indicate that Japan has experienced significant progress in providing Muslim-friendly facilities, such as halal food, prayer spaces, and inclusive tourism services. However, several challenges remain, including limited public understanding of the needs of Muslim tourists, the lack of a fully integrated halal certification system, and language and cultural barriers. Nevertheless, these challenges can still be managed, as the Japanese government supports the presence of Muslim communities in Japan as part of its global engagement. The findings reveal that Japan has made significant progress in developing Muslim-friendly tourism through the provision of halal food, prayer facilities, digital information services, and inclusive tourism infrastructure.